Tanah untuk sanitasi lingkungan terhadap limbah cair industri - Susilowati, Susilowati (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1996)
Industrial waste management, especially industrial waste water usually is carried out using a high mechanical system, which is need a relative expensive cost. This is not adjustable for small and medium scale industry. The industrial waste, especially industrial waste water is a potential element for environmental degradation. Actually some of specific matter on industrial waste water is possible to use for agriculture to increase the essential soils matter and can improve the physical and chemical soils fertility as a cheap fertilizer. The main matter and the form process of the soils give a special character and varienty. This character influences the physical and chemical quality of soils. With the presence of this character and quality, soils have three functions : as a filter, as a buffer and as a system changer. Based on the soils charactistic and quality, soils can be useful for environmental sanitation of industrial waste water. Soils can be used another efficient alternative for waste water industrial management, especially for small and medium scale industry. ABSTRAK Pengelolaan limbah industri, terutama limbah cair biasanya dilakukan dengan sistem mekanis tinggi yang membutuhkan biaya relatif mahal. Kenyataan ini mengakibatkan industry kecil dan skala menengah tidak mungkin melaksanakannya. Limbah industry, utamanya limbah cair industri merupakan usnur potensial bagi ancaman kelestarian kemampuan lingkungan. Namun sebetulnya unsur-unsur tertentu dalam limbah cair tersebut punya kemungkinan untuk dimanfaatkan oleh sector pertanian, yaitu dapat menambah kandungan nilai hara dalam tanah. Berarti bermanfaat sebagai bahan untuk perbaikan kesuburan fisika dan kimiawi tanah, dengan demikian berfungsi sebagai cara pemupukan yang murah. Sifat dan jenis tanah sangat ditentukan oleh batuan induk dan proses pembentukan tanah itu sendiri. Keadaan ini akan berpengaruh terhadap sifat-sifat fisika dan kimiawi tanah.